Whole-genome sequence of bioactive streptomycete derived from mangrove forest in Malaysia, Streptomyces sp. MUSC 14 - Hooi-Leng Ser; Loh Teng-Hern Tan; Wen-Si Tan; Wai-Fong Yin; Kok-Gan Chan (Progress in Microbes and Molecular Biology)
The contribution of streptomycetes to human health is undeniably important and significant, given that these filamentous microbes can produce interesting compounds that can be used to cure deadly infections and even cancer. Isolated from the east coast of Peninsular Malaysia, Streptomyces sp. MUSC 14 has shown significant antioxidant capacity. The current study explores the genomic potential of MUSC 14 via a genome mining approach. The genome size of MUSC 14 is 10,274,825 bp with G + C content of 71.3 %. AntiSMASH analysis revealed a total of nine biosynthetic gene clusters (with more than 80 % similarities to known gene clusters). This information serves as an important foundation for subsequent studies, particularly the purification and isolation of bioactive compounds by genetic manipulation techniques.